PENERAPAN STRATEGI PEMBELAJARAN MEANS ENDS ANALYSIS (MEA) TERHADAP PENINGKATAN KEMAMPUAN BERFIKIR KRITIS MATEMATIS SISWA - Yuyu Hayunah; Ricki Yuliardi; Abdul Rosyid (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
Application of Learning Strategies Means Ends Analysis (MEA) To Increase Students Critical Thinking Skill Mathematically. The background of this research is two improve student critical thinking mathematically using learning strategies Means Ends Analysis. From the result of the pretest known that the mean score of critical thinking mathematically control class is 16.04, and the experimental class is 18.275. Meanwhile, it is known that the result of the posttest mean score of critical thinking mathematically control class is 62.03 and the mean score critical thinking mathematically experimental class is 78.5. From the analysis of pretest and posttest samples can be concluded that the study of mathematics by using learning strategies Means Ends Analysis is better than the ability of critical thinking mathematical students by using conventional learning strategies. The increased ability to think critically mathematical experimental class in middle category